Facile and High-yield Synthesis of N-doped Carbon Quantum Dots from Biomass Quinoa Saponin for the Detection of Co2+ - Cuo Zhou; Shunwei Wu; Shenghui Qi; Weijun Song; Chunyan Sun (Journal of Analytical Methods in Chemistry)
Hydrothermal synthesis of carbon quantum dots (CQDs) from natural biomass is a green and sustainable route for CQDs applications in various fields. In this work, the preparation and characterization of CQDs based on quinoa saponin were investigated. The optimum synthetic conditions determined by orthogonal experiments were as follows: 2 g quinoa saponin powder and 0.04 mol ethylenediamine reacted at 200°C for 10 h. The relative fluorescence quantum yield (QY = 22.2%) can be obtained, which is higher than some results reported in the literatures. The prepared CQDs had a small and uniform size (∼2.25 nm) and exhibited excitation wavelength-dependent blue light emission behavior. The CQDs displayed excellent sensitivity for Co2+ detection along with good linear correlation ranging from 20 to 150 µM and the detection limit of 0.49 µM. The CQDs prepared in this experiment were successfully implanted into soybean sprouts for fluorescence imaging. The sprouts could grow healthily even soaked in the CQDs solution for two weeks, demonstrating the low toxicity of the CQDs. The advantages of the CQDs, such as low cost, ease of manufacture, nontoxicity, and stability, have potential applications in many areas such as metal ion detection and biosensing.